Slice of Maine RFD Maine - Phippen, Sanford; Kennedy, Tami.; Rand, Janice; Woodward, Nick.; Maine Public Television; United States. Rural Development ([Lewiston, Me.] : Maine Public Television, 1997)
A slice of the best of life in rural Maine. The Corea Post Office has made a permanent stamp on the hearts of those who live in the village of Corea. We'll hear how life just wouldn't be the same without the Franklin Trading Post at the center of town. We get a peek at Lucerne Maple Products in East Holden where smoke from the sugar shack signals the turn of winter into spring.
Program title from cassette label; program number from descriptive sheet.
Mini-series created by and originally broadcast on Maine Public Television. Funded by a television demonstration grant from Rural Development, part of the USDA. More information is available on the WWW site: www.mpbc.org.
Segment producers: Tami Kennedy, Janice Rand, Nick Woodward.
Hosted by Sandy Phippen.
VHS.
Closed captioned for the hearing impaired.
Keywords: Rural industries -- Maine; Community life -- Maine; Documentary television programs -- Maine; Maine -- Rural conditions; Maine -- Social life and customs